AB0569 Effects of tocilizumab in combination with non biologic DMARDS on early improvement of anemia and fatigue in adult patients with moderate to severe active rheumatoid arthritis. (23rd January 2014) - Foti, R.; Russo, R.; Malavolta, N.; Bravi, E.; Semeraro, A.; Limonta, M.; Muratore, M.; Pozzi, M.R.; Spinello, M.; Bernardoni, M.C.; Versace, F.; Rogai, V.
Abstract : Background: A significant number of RA patients (pts) have low haemoglobin (Hb) levels. Normalisation of Hb in anaemic RA pts may be a suitable marker of improvement in disease activity, as well as improvement of fatigue. Objectives: The main objective of this phase IIIb, national, multicentric, open-label, prospective, single-arm study was to assess the effects of TCZ in combination with DMARDs on anaemia and fatigue over 24 weeks of treatment in pts with moderate-severe active RA who had an inadequate response to DMARDs. Methods: TCZ 8mg/kg IV was given every 4 wks for a total of 6 infusions. Changes from baseline of anemia and fatigue at wk 4, evaluated as change in Hb levels and FACIT-Fatigue questionnaire, respectively, were the primary endpoints. Secondary efficacy endpoints were measured up to 24 wks from the start of treatment. Adverse events (AEs) and lab tests were the safety measures. Paired t test was used for the analysis of changes from baseline. Results: A total of 105 pts (mean age 55 years, 85% females) received TCZ (ITT population) and 13 (12.4%) were discontinued (AEs was the leading cause of withdrawal, 7 pts). Mean (±SD) Hb levels and FACIT-Fatigue score significantly increased from baseline to wk 4 (+0.40±0.78 g/dl and +8.76±8.83, respectively, p<0.001 for both variables). Consistent findings were observed in the per-protocol sample (85 pts). Hb levels and fatigue improved from 2 wks (+0.47±0.69 g/dL and +7.11±8.40, respectively, p<0.001 for both) up to wk 24 (+0.64±1.20 g/dL and +10.84±11.02, respectively, p<0.001 for both). An increase in Hb levels ≥1 g/dl from baseline to wk 24 was observed in 31.4% of pts. All individual ACR score parameters decreased from baseline (p<0.001 for all parameters at any time point). ACR20/50/70 responses were observed in 81.0%, 59.0% and 42.9% of pts, respectively. Mean DAS-28 significantly decreased from baseline to wk 24: a good and moderate EULAR response at wk 24 was observed in 63.8% and 23.8% of pts, respectively, whereas 12.4% did not respond. A DAS-28 score <2.6 was achieved in 49.5% of pts. AEs were reported in 61.9% of pts (drug-related in 41.9%): 2 of them were serious (chest pain and pneumonia). Dose modification due to AEs was required in 12.4% of pts. Clinically-significant increases in transaminases and cholesterol were observed in 5% of pts. Leukopenia and thrombocytopenia were reported in 2% of pts. There were no important changes from baseline in the other lab safety parameters. Conclusions: A 24-wk treatment with TCZ 8mg/kg in combination with DMARDs in pts with moderate-severe active RA not responsive to DMARDs therapy was associated with rapid and sustained improvements of anaemia and fatigue, and good clinical response rates with the safety profile of TCZ consistent with that previously reported. Disclosure of Interest: R. Foti: None Declared, R. Russo: None Declared, N. Malavolta: None Declared, E. Bravi: None Declared, A. Semeraro: None Declared, M. Limonta: None Declared, M. Muratore: None Declared, M. R. Pozzi: None Declared, M. Spinello: None Declared, M. C. Bernardoni: None Declared, F. Versace: None Declared, V. Rogai Employee of: Roche S.p.a.